1979
DOI: 10.1111/j.1432-1033.1979.tb13167.x
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase from the Fungus Aspergillus nidulans

Abstract: The DNA-dependent RNA polymerase I (or A) from the lower eukaryote Aspergillus niduluns has been purified on a large scale to apparent homogeneity by homogenizing the fungal hyphae in liquid nitrogen, extraction of the enzyme at high salt concentration, precipitation of RNA polymerase activity with polymin P (a polyethylene imine), elution of the RNA polymerase from the polymin P precipitate, ammonium sulphate precipitation, molecular sieving on Bio-Gel A-I .5m, binding to ion-exchangers and DNA-cellulose affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…crassa are impermeable to these inhibitors (Tisdale & DeBusk, 1972) so the lack of inhibition might be a question of impermeability. However, Stunnenberg et al (1979) have shown that even in vitro three RNA polymerases of A. niduldns are largely or completely insensitive to a-amanitin.…”
Section: Examples Of the Effects Of Various Treatments On Nucleic Acimentioning
confidence: 99%
“…crassa are impermeable to these inhibitors (Tisdale & DeBusk, 1972) so the lack of inhibition might be a question of impermeability. However, Stunnenberg et al (1979) have shown that even in vitro three RNA polymerases of A. niduldns are largely or completely insensitive to a-amanitin.…”
Section: Examples Of the Effects Of Various Treatments On Nucleic Acimentioning
confidence: 99%
“…DEAE-Sephacel and heparin-Sepharose CL-6B (Pharmacia) were prewashed and equilibrated as described (15). The density gradient of 5-20% sucrose was made up in 500 mM NaCl/50 mM Tris HCI, pH 7.9/ 5 mM MgCI2/1 mM EDTA/0.5 mM dithiothreitol/0.1 mM PhMeSO2F and run for 40 hr at 36,000 rpm in a Beckman SW 40.1 rotor at 4°C.…”
mentioning
confidence: 99%
“…To enrich the active component, we fractionated the protein extract by heparin-Sepharose chromatography (14,15). The column was equilibrated with protein storage buffer (100 mM NaCl, final concentration), and the protein fraction was applied onto the column in the same buffer.…”
mentioning
confidence: 99%